STUDENTS’ PERCEPTION ON USING SCHOOLOGY APPLICATION IN LEARNING ENGLISH DURING PANDEMIC COVID-19 - Febrianti Febrianti; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to identify and describe the students’ perception on using Schoology application in learning English during pandemic Covid-19. The population of this research is the second year students of SMP Cendana Pekanbaru. The number of sample is 44 students selected by using cluster random sampling technique. Data of this research were collected through an online questionnaire using Google form and distributed via WhatsApp Group. The research analyzed by using SPSS Ver.23 and Microsoft Excel then explained descriptively. Based on the results of this research, the students’ perception levels in terms of Students’ Perception on Utilizing Schoology in Learning English during Pandemic Covid-19 (X1) was in very good category (82.8%), Students’ Perception about Benefits of Using Schoology in Learning English during Pandemic Covid-19 (X2) was in good category (76%), Students’ Perception about Challenges on Using Schoology in Learning English during Pandemic Covid-19 (X3) was in mediocre category (58.9%), and Students’ Perception of Satisfaction by Using Schoology in Learning English during Pandemic Covid-19 (X4) was in good category (67%). The results shows the average of all scores in general was in good category (71.18%). It means the students’ positively accepted Schoology as a good application a platform in learning English during pandemic Covid-19. Students’ Perception on Utilizing Schoology in Learning English during Pandemic Covid-19 (X1) has the highest percentage (82.8%) which means that students agree that Schoology is easy to use, Schoology has interesting features that support teaching and learning activities. This study implies that the second year students of SMP Cendana Pekanbaru have a good perception on using Schoology in learning English during pandemic Covid-19.Key Words: Perception, Schoology, Pandemic Covid-19.